Association between peroxisome proliferator-activated receptor-alpha, delta, and gamma polymorphisms and risk of coronary heart disease: A case–control study and meta-analysis. Issue 32 (August 2016) - Qian, Yufeng; Li, Peiwei; Zhang, Jinjie; Shi, Yu; Chen, Kun; Yang, Jun; Wu, Yihua; Ye, Xianhua
Abstract: Objectives: Risk of coronary heart disease (CHD) has been suggested to be associated with polymorphisms of peroxisome proliferator-activated receptors (PPARs), while the results were controversial. We aimed to systematically assess the association between PPAR polymorphisms and CHD risk. Methods: A case–control study with 446 subjects was conducted to evaluate the association between CHD risk and C161T polymorphism, which was of our special interest as this polymorphism showed different effects on risks of CHD and acute coronary syndrome (ACS). Meta-analyses were conducted to assess all PPAR polymorphisms. Either a fixed- or a random-effects model was adopted to estimate overall odds ratios (ORs). Results: In the case–control study, T allele carriers of C161T polymorphism were not significantly associated with CHD risk (Odds ratio (OR) = 0.74, 95% confidence interval (CI) 0.47–1.15, P  = 0.19), while T allele carriers showed higher risk of ACS (OR = 1.63, 95% CI 1.00–2.65, P  = 0.048). The meta-analysis indicated that compared with CC homozygous, T allele carriers had lower CHD risk (OR = 0.69, 95% CI 0.59–0.82, P  < 0.001) but higher ACS risk (OR = 1.43, 95% CI 1.09–1.87, P  = 0.010). Three other polymorphisms were also found to be significantly associated with CHD risk under dominant model: PPAR-alpha intron 7G/C polymorphism ( CC + GC vs GG, OR 1.42, 95% CI 1.13–1.78, P  = 0.003), L162V polymorphism ( VV + LV vs LL, OR 0.74, 95% CI 0.56–0.97, P  = 0.031), and PPAR-delta +294T/C polymorphism ( CC + TC vs TT, OR 1.51, 95% CI 1.12–2.05, P  = 0.007). Conclusions: The results suggested that PPAR-alpha intron 7G/C and L162V, PPAR-delta +294T/C and PPAR-gamma C161T polymorphisms could affect CHD susceptibility, and C161T polymorphism might have different effects on CHD and ACS. Abstract : Supplemental Digital Content is available in the text